Penerapan Aplikasi Pendaftaran Antrean Paspor Online dalam Upaya Meningkatkan Pelayanan Publik di Bengkulu - Deni Triyanto; Kismartini Kismartini; Henny Aprianty; Puteri Novelia (Universitas Medan Area, 2022)
This study aims to determine and understand the application of the Online Passport Queue Registration Application (APAPO) in an effort to improve public services in Bengkulu City at the Class I Immigration Office at Bengkulu Immigration Checkpoints. The study used a qualitative descriptive method, with 10 research informants, consisting of 4 Immigration Office informants and 6 community informants. Data analysis used qualitative analysis. The results of the study show that: (1) The implementation of e-government at the Immigration Office Class I TPI Bengkulu has been going quite well because there are still obstacles, namely complicated and limited service quotas; (2) Passport services at the Immigration Office Class I TPI Bengkulu through the use of online passport services are of Sufficient Quality; and (3) The supporting factors in the application of electronic government in improving the quality of online passport making services are the existence of clear regulations, clear service needs and an adequate number of personnel. While the inhibiting factors in implementing e-government in improving the quality of online passport making services are the complexity of the APAPO application, the limited number of queue quotas and sometimes incomplete requirements, so that services cannot be implemented.